Reproduction of Varroa destructor and offspring mortality in worker and drone brood cells of Africanized honey bees - Calderón Fallas, Rafael A. (2012)
Varroa destructor is known to be the most serious parasite of Apis mellifera worldwide. In order to reproduce varroa females enter worker or drone brood shortly before the cell is sealed. From March to December 2008, the reproductive rate and offspring mortality (mature and immature stages), focusing on male absence and male mortality of V. destructor, was investigated in naturally infested worker and drone brood of Africanized honey bees (AHB) in Costa Rica. Data were obtained from 388 to 403 single infested worker and drone brood cells, respectively. Mite fertility in worker and drone brood cells was 88. 9 and 93. 1%, respectively. There was no difference between the groups (X 2 = 3. 6, P = 0. 06). However, one of the most significant differences in mite reproduction was the higher percentage of mites producing viable offspring in drone cells (64. 8%) compared to worker cells (37. 6%) (X 2 = 57. 2, P < 0. 05). A greater proportion of mites in worker brood cells produced non-viable female offspring. Mite offspring mortality in both worker and drone cells was high in the protonymph stage (mobile and immobile). A significant finding was the high rate of male mortality. The worker and drone brood revealed that 23. 9 and 6. 9%, respectively, of the adult male offspring was found dead. If the absence (missing) of the male and adult male mortality are taken together the percentage of cells increased to 40. 0 and 21. 3% in worker and drone cells, respectively (X 2 = 28. 8, P < 0. 05). The absence of the male or male mortality in a considerable number of worker cells naturally infested with varroa is the major factor in our study which reduces the production of viable daughters in AHB colonies in Costa Rica.